Suitable MPTS for Sodic Soils of Central Plain Zone of Uttar Pradesh - Khan, S.A.; Shukla, I.N. (Indian Journal of Agroforestry, 2020)
Multi purpose trees and shrubs (MPTS) can find place on sodic soil where annual crops can not be grown due to higher pH and electric conductivity. The Uttar Pradesh possess about 1.2 million hectare sodic soil. Keeping in view the seriousness of sodicity, the present study was undertaken in Sodic Soils at Regional Research Station, Dalip Nagar, C.S. Azad University of Agriculture & Technology, Kanpur during 1989-2000. By the plantation of MPTS, soil pH and EC was decreased upto 8.2 and 0.2 mmhos/ cm from initial value of 10.5 and 0.736 mmhos/cm, respectively after 11 years experimentation. The soil organic carbon, available phosphorus and available potash was increased. Among the tree species tested, Acacia nilotica, Albizia procera, Leucaena leucocephala, Azadirachta indica and Eucalyptus hybrids were found most suitable tree species for rehabilitation of sodic soils and to maintain eco-friendly systems.